ANALISIS FAKTOR YANG MEMENGARUHI ADVERSITY QUOTIENT PERAWAT DI RUMAH SAKIT UMUM SINAR HUSNI MEDAN - Meta Nofita; Thomson P Nadapdap; Asriwati - (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2021)
Low nurse adversity quotient will affect nursing services in a health facility. This study aims to analyze the factors that influence nurses' Adversity Quotient at Sinar Husni General Hospital, Medan. This type of research is an analytic survey with a cross sectional study design. The study was conducted at the Sinar Husni General Hospital, Medan. The sample in this study used a total sampling technique so that the sample were all nurses at Sinar Husni General Hospital, Medan, as many as 71 people. To analyze the data used the chi-square test and logistic regression. Based on the results of the study it can be concluded that there is a genetic influence on nurses' Adversity Quotient in the inpatient room of the Sinar Husni General Hospital in Medan, there is an influence of beliefs on the Adversity Quotient of nurses at the Sinar Husni General Hospital in Medan, there is an influence of talent on the Adversity Quotient of nurses at the Hospital General Sinar Husni Medan, there is an influence of willingness on nurses' Adversity Quotient at Sinar Husni General Hospital Medan, there is an environmental effect on nurses' Adversity Quotient at Sinar Husni General Hospital in Medan, there is a character effect on nurses' Adversity Quotient at Sinar Husni General Hospital, Medan. Based on the conclusions above, it is recommended that hospitals can consider developing HR by including the Adversity Quotient development program in the annual plan in addition to professional skills and knowledge training. In addition, the hospital can also review the recruitment system by including an assessment of the level of one's Adversity Quotient in a psychological test as one of the considerations of employee recruitment.